COMPARATIVE STUDY OF PATIENT SATISFACTION WITH IMPLANT-RETAINED VS. CONVENTIONAL OVERDENTURES - Dr. Sheema Shakir; Dr. Jawad Rafique; Dr. Samia Manzar; Dr. Tabassum Ajmal; Dr. Ambreen Usmani (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: The purpose of this study was to assess how patient satisfaction differs with implant-retained mandibular overdentures compared with conventional mandibular overdentures. The primary focus was on satisfaction levels related to comfort, stability, chewing, speech, esthetic appeal, and the overall impact on the quality of life.Methods: This cross-sectional study was conducted under the Department of Prosthodontics at Khyber College of Dentistry in Peshawar and Peshawar Medical and Dental College, from January 2021 to January 2023. From the population, 80 patients were recruited, consisting of 40 individuals per each group. Aspects of denture satisfaction such as functional performance and psychological impact were retrieved using a structured questionnaire. An additional clinical examination was conducted to evaluate the maintenance and tissue response to the prosthesis. The statistical package for social sciences (SPSS) version 25 was used to perform the statistical analysis with the level of significance at p < 0.05.Results: Across all examined parameters, patients with implant-retained overdentures reported greater satisfaction and psychosocial impacts than those with conventional overdentures. These patients experienced improved chewing comfort, denture stability, better speech, as well as greater overall satisfaction. Social self-confidence was also reported to be better in the implant group, along with a more favorable effect on daily life. The results, however, did not depend on the demographic and clinical characteristics of the subjects as both groups were comparable in these respects. Most, if not all, outcomes were in favor of the implant-supported prostheses.Conclusion: Implant-retained overdentures have significant benefits regarding the comfort, function, and the quality of life of the patients. Whenever possible, they should be regarded as the primary choice for edentulous patients for improved prosthesis function and overall satisfaction.